In vitro Activity of Lefamulin Against the Common Respiratory Pathogens Isolated From Mainland China During 2017–2019 - Wu, Shi; Zheng, Yonggui; Guo, Yan; Yin, Dandan; Zhu, Demei; Hu, Fupin (Frontiers in Microbiology, 2020)
Purpose: Lefamulin is a novel antibiotic approved by the U.S. Food and Drug Administration in 2019 for the treatment of community-acquired bacterial pneumonia (CABP). In this study we evaluated the in vitro antimicrobial activity of lefamulin in order to better understand its antibiogram. Methods: The test strains were isolated from patients across China during the period from 2017 to 2019, including 634 strains of respiratory pathogens. The minimum inhibitory concentrations (MICs) of lefamulin and comparators were determined by broth microdilution method. Results: Lefamulin showed potent activity against Streptococcus pneumoniae and Staphylococcus evidenced by 100% inhibition at 0.25 mg/L, and favorable MIC50/90 (0.125/0.125 mg/L) against S. pneumoniae (penicillin MIC ≥ 2 mg/L), MIC50/90 (≤ 0.015/0.125 mg/L) against methicillin-resistant S. aureus, and MIC50/90 (≤ 0.015/0.06 mg/L) against methicillin-resistant S. epidermidis. Lefamulin also had good activity against Streptococcus pyogenes and Streptococcus agalactia (MIC50/90: ≤ 0.015/≤ 0.015 mg/L), β-lactamase-producing Haemophilus influenzae (MIC50/90: 0.5/1 mg/L), β-lactamase-negative H. influenzae (MIC50/90: 1/1 mg/L), Moraxella catarrhalis (MIC50/90: 0.25/0.25 mg/L), and Mycoplasma pneumoniae (MIC50/90: 0.03/0.03 mg/L) regardless of resistance to azithromycin. Lefamulin was generally more active than the comparators against the test strains. Conclusions: In summary, lefamulin has good and broad-spectrum coverage of respiratory pathogens (methicillin-sensitive and -resistant Staphylococcus, S. pneumoniae, β-hemolytic Streptococcus, H. influenzae, M. catarrhalis and M. pneumoniae). In vitro activity supports the use of lefamulin in the treatment of CABP in China.